A randomised controlled trial of intrathecal blockade versus peripheral nerve blockade for day‐case knee arthroscopy. (6th January 2016) - Ambrosoli, A. L.; Chiaranda, M.; Fedele, L. L.; Gemma, M.; Cedrati, V.; Cappelleri, G.
Summary: We allocated 100 patients scheduled for day‐case knee arthroscopy to unilateral spinal anaesthesia with 40 mg intrathecal hyperbaric prilocaine or to ultrasound‐guided femoral‐sciatic nerve blockade with 25 ml mepivacaine 2%, 50 participants each. The median (IQR [range]) time to walk was 285 (240–330 [160–515]) min after intrathecal anaesthesia vs 328 (280–362 [150–435]) min after peripheral nerve blockade, p = 0.007. The median (IQR [range]) time to home discharge was 310 (260–350 [160–520]) min after intrathecal anaesthesia vs 335 (290–395 [190–440]) min after peripheral nerve blockade, p = 0.016. There was no difference in time from anaesthetic preparation to readiness for surgery.